Strategi Peningkatan Omset Penjualan Pedagang Pakaian Melalui Marketing Mix Studi Pada Pasar Muntilan, Kabupaten Magelang - Emy Setyawati; andhatu achsa (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This research aims to evaluate the marketing strategy that has been applied by clothing traders in Muntilan Market, Magelang using marketing mix (4P) and SWOT analysis. This type of research uses qualitative descriptive and observation, interview, and literature studies as a method of data collection. The results of the analysis of marketing mix strategy applied by clothing traders in Muntilan Market are: providing a variety of product options, setting small profits to keep prices affordable, providing good service and neat preparation of goods, as well as promotions through direct and word of mouth offers. Based on internal and external analysis, clothing traders in Muntilan Market show the position of growth strategy. Where the right strategy is to maximize strength and take advantage of opportunities (SO).